Paradigms of combinatorial optimization - Paschos, Vangelis Th. (London : ISTE, Ltd., 2014)
Combinatorial optimization is a multidisciplinary scientific area, lying in the interface of three major scientific domains: mathematics, theoretical computer science and management. The three volumes of the Combinatorial Optimization series aim to cover a wide range of topics in this area. These topics also deal with fundamental notions and approaches as with several classical applications of combinatorial optimization. Concepts of Combinatorial Optimization, is divided into three parts:- On the complexity of combinatorial optimization problems, presenting basics.
3.2.3. Empty covering3.2.4. Bicriteria models; 3.2.5. Covering with multiple resources; 3.3. Discrete problems; 3.3.1. p-Center; 3.3.2. p-Dispersion; 3.3.3. p-Median; 3.3.3.1. Fixed charge; 3.3.4. Hub; 3.3.5. p-Maxisum; 3.4. On-line problems; 3.5. The quadratic assignment problem; 3.5.1. Definitions and formulations of the problem; 3.5.2. Complexity; 3.5.3. Relaxations and lower bounds; 3.5.3.1. Linear relaxations; 3.5.3.2. Semi-definite relaxations; 3.5.3.3. Convex quadratic relaxations; 3.6. Conclusion; 3.7. Bibliography; Chapter 4: MiniMax Algorithms and Games; 4.1. Introduction.
Print version record.
5.3.4. Bin packing: one-phase non-level heuristics.
Includes bibliographical references and index.
Keywords: Combinatorial optimization; Programming (Mathematics); Combinatorial optimization; Game theory; Mathematics; MATHEMATICS -- Applied; MATHEMATICS -- Probability & Statistics -- General; Combinatorial optimization; Programming (Mathematics); Electronic books